On the background of enhanced stability and reusability of enzymes in ionic liquids. (23rd November 2007) - Fehér, E.; Major, B.; Bélafi-Bakó, K.; Gubicza, L.
Abstract : The ability of ILs (ionic liquids) to provide an environment of increased stability and, in this way, improve the recyclability of enzymes has been studied. The description of this phenomenon is not easy; there are several approaches for explanation. In this mini-review, the results from different research groups are summarized, with the aim of explaining the strong stability effect of ILs on several enzymes. Spectroscopic methods (e.g. fluorescence and CD, IR spectroscopy, mass spectroscopy and NMR) and investigations of polarity and kosmotropicity of ions are promising methods. Since higher stability means that we may be able to reuse enzymes more times, the recyclability of enzymes was also in the focus. From this point of view, the advantages and disadvantages of applying monophasic or biphasic systems are discussed too, presenting the coupled techniques as well.